Development, validation and the effects of culturally specific guided imagery and progressive muscle relaxation audio for patients with functional abdominal bloating - Shen, Vincent Tee Wei (2022)
The Rome Working Team had recommended the use of brain-gut behaviour therapies in treating Disorders of Gut-brain Interaction (DGBI). Mind-body techniques, including Guided Imagery (GI) and Progressive Muscle Relaxation (PMR) has been long used as therapeutic modalities for various disorders. However, its relevance and efficacy in treating patients with DGBI in Malaysia is still unexplored. The study herein aimed to develop, validate, and explore the effects of audio-based GI and PMR techniques on patients with functional abdominal bloating. The study can be divided into three main phases. Phase 1 involves the development and validation of culturally specific GI and PMR audios. Initially, the audio scripts were drafted according to literature reviews and findings from in-depth interviews with participants diagnosed with bloating based on the Rome IV criteria. Scripts were validated using psychometric (content and face validity index) and physiological parameters [(brain event-related potentials (ERP) & heart rate variability (HRV)]. 35/63 participants completed the in-depth interview. The findings include the frequent usage of ‘balloon’ as a synonymous imagery description for bloating, of which the sensation of bloatedness is association with pain. Eventually, the scripts were narrated and compiled with a validated musical backgrounds. Overall, the content and face validity index for PMR and GI ranged from 0.92 - 1.00. For ERP and HRV, 17/20 participants were analysed. For ERP, there were significant difference between GI and PMR for alpha waves (p=0.029), delta waves (p=0.029) and between PMR and control for delta waves (p=0.014). For HRV, both GI and PMR exhibited similar autonomic responses over controls with significant difference among Low Frequency/High Frequency ratio, Total Power, Low Frequency, and Respiratory Rate (overall p<0.05). Phase 2 involves the development and validation of a mobile application that helps to facilitate the delivery of the audios. The validation process involves inviting expert panels, volunteers, and participants with bloating to rate and navigate the application. Feedbacks and comments were noted. Revision was made accordingly. The findings from the Malay-version mHealth App Usability Questionnaire (MAUQ) indicate satisfactory levels (5.45-5.85/7.00). Furthermore, 132 participants were randomly assigned into three groups (GI, PMR, control), each receiving different audios. Findings from 96 participants were analysed. Significant differences were observed in terms of time effect among the Severity General, Severity in 24 hours, Quality of Life, Health-Promoting Behaviour, and anxiety variables. Only anxiety showed significant changes among the group (p=0.027) and time*group interaction (p<0.001).